2011
DOI: 10.1029/2010jg001365
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and temperature dependence of branched glycerol dialkyl glycerol tetraethers in recent lacustrine sediments from China and Nepal

Abstract: [1] Glycerol dialkyl glycerol tetraether (GDGT) membrane lipids in surface sediments from 24 lakes in China and Nepal were analyzed. The result shows that branched GDGT lipids occur widely in the studied lake sediments. The different distribution of branched GDGTs between the Chinese soils from Weijers et al. (2007b) and the Chinese lake sediments indicates that the branched GDGTs in the lacustrine sediment are the mixture of allochthonous and autochthonous branched GDGTs. Our result supports the suggestion th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
198
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(218 citation statements)
references
References 47 publications
18
198
2
Order By: Relevance
“…It is well known that brGDGT soil calibrations differ from those reported for aquatic environments (Tierney et al, 2010;Zink et al, 2010;Pearson et al, 2011;Sun et al, 2011;Loomis et al, 2012). However, calibrations for river water have not yet been reported.…”
Section: Implications For the Mbt'/cbt Proxymentioning
confidence: 83%
See 1 more Smart Citation
“…It is well known that brGDGT soil calibrations differ from those reported for aquatic environments (Tierney et al, 2010;Zink et al, 2010;Pearson et al, 2011;Sun et al, 2011;Loomis et al, 2012). However, calibrations for river water have not yet been reported.…”
Section: Implications For the Mbt'/cbt Proxymentioning
confidence: 83%
“…10b), with the largest changes observed for the IPL-derived brGDGTs. MBT' (and MBT) are also related to temperature in aquatic systems (Tierney et al, 2010;Zink et al, 2010;Pearson et al, 2011;Sun et al, 2011). Hence, MBT' could be used as evidence for in situ production of brGDGTs in the river as MBT' would then follow the changes in temperature over the annual cycle, whereas in case of a dominant soil origin for the brGDGTs, this would not be expected because of their residence time in soils .…”
Section: Sources Of Gdgts In Tagus River Spm and Riverbank Sedimentsmentioning
confidence: 99%
“…In the Weijers et al (2007a) the original soil calibration had an r 2 of 0.77 with a standard error of 5°C (Weijers et al, 2007b). In a global lakes calibration, Sun et al (2011) reported r 2 = 0.62, with a standard error of 5.2°C across the whole data set, and r 2 = 0.73 with an error of 4.3°C when highly alkaline lakes were excluded. A recent recalibration of the MBT/CBT for soils reported an r 2 of 0.59 with a standard error of 5°C (Peterse et al, 2012).…”
Section: Mbt/cbt Proxymentioning
confidence: 91%
“…Fig. 9 shows plots of measured vs calculated MAT using our speleothem based calibration, with the relevant regression lines from the equations of Sun et al (2011) and Weijers et al (2007a). The speleothem correlations have a lower slope than either of the other calibra- tions, and produces intermediate calculated temperatures, which begin to converge with the lakes calibration in colder samples (<10°C) and the soils calibration in hotter climates (>20°C).…”
Section: Mbt/cbt Proxymentioning
confidence: 99%
See 1 more Smart Citation